2021
DOI: 10.1016/j.eurpolymj.2021.110269
|View full text |Cite
|
Sign up to set email alerts
|

Effective elastin-like recombinamers coating on poly(vinylidene) fluoride membranes for mesenchymal stem cell culture

Abstract: Bone's inherent piezoelectricity is a key factor in regulating bone growth and mesenchymal stem cells (MSCs) fate towards the osteogenic lineage. The piezoelectric polymer poly(vinylidene) fluoride (PVDF) was thus used to manufacture electroactive membranes by means of non-solvent induced phase separation (NIPS), producing porous membranes with approximately 90 % of phase for MSCs culture. The combination of the porous surface and PVDF hydrophobicity hinders cell adhesion and requires a coating to improve cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…For example, cell adhesion is promoted by Review Biomaterials Science the use of materials that are known to have adhesive properties. Arginine-glycine-aspartic acid (RGD) [74][75][76] and catechol groups, 77,78 either acting as an assembly component or as a partial structure of the polymers, have been used to support cell and protein adhesion due to the enriched interactions between surfaces and cells.…”
Section: Planar Substratesmentioning
confidence: 99%
“…For example, cell adhesion is promoted by Review Biomaterials Science the use of materials that are known to have adhesive properties. Arginine-glycine-aspartic acid (RGD) [74][75][76] and catechol groups, 77,78 either acting as an assembly component or as a partial structure of the polymers, have been used to support cell and protein adhesion due to the enriched interactions between surfaces and cells.…”
Section: Planar Substratesmentioning
confidence: 99%
“…6,7,14 Despite its potential, there is limited research addressing the effect of electrical stimulation produced by the piezoelectric response of the material to mechanical stimuli like vibration, compression, and stretching 15 ; and these type of stimuli are commonly applied during cell culturing via bioreactors. 16,17 Another approach has been implemented to mechanically stimulate tissues by using the reverse piezoelectric effect, which involves the use of low frequency alternating current; it was demonstrated that new bone formation was induced in vivo as a result of mechanical stimulation and gene expression of osteoblasts in culture and metabolic activity were increased. 6 Furthermore, other in vivo study by using mechanical stimulation achieves bone growth.…”
mentioning
confidence: 99%